A GENRE-BASED MODEL FOR TEACHING HOW TO WRITE A DISCUSSION TO STUDENTS OF ENGLISH AS A FOREIGN LANGUAGE - Liliek Soepriatmadji (Dinamika Bahasa dan Budaya, 2008)
Teaching how to write (a discussion) in a foreign language context is not an easy task due to the different levels, motivation, and experience of the target language. However the development of genre literacy has recently provided an attempt to create a new pedagogical space in the writing classroom. It is, therefore, this article elaborates how one should develop a genre-based model for teaching how to write a discussion by employing its social function, generic structure, lexicogrammatical features, and the teaching cycles.   Key words: genre-based, social function, generic structure, lexicogrammatical features, and teaching cycles.